ENDONASAL THERAPY IN PRE - AND POSTOPERATIVE PERIOD IN PATIENTS WITH DIAGNOSIS OF ADENOIDITIS - Абілова, Ф.А. (World of Medicine and Biology, 2015)
The purpose of the study. Explore the possibility of reducing the symptom complex related to inflammation of pharyngeal tonsils and reduce the recurrence of adenoids with the above mentioned symptoms. Methods. Under our supervision there were patients aged 2 to 15 years. Of these, 87 girls and 105 boys. All patients diagnosed with adenoiditis. Of these, 27 patients were accompanied by adenoids with otitis media, 2 cases of chronic otitis media, sinusitis 17 patients, 25 chronic tonsillitis. It should be noted, although, all patients operative treatment, in the beginning my parents were to surgery wary. Agreed that patients should be a topical treatment in the form of drops. On the use of antimicrobials of patients were divided into three groups: the first group used octenisept, in the second group - the 1% solution dioksidina, in the third group - 10-20% solution sulfatsila sodium. Besides defined control group without any therapy produced only adenotomy. It should be noted that at the location of the lymphadenoid tissue in the nasopharynx, we identified 3 forms of the adenoids. Adenoids I form - included patients with adenoid vegetation are closer to hounam, II form –lymphadenoid tissue are mainly determined on the vault of the nasopharynx, III forms of lymphadenoid tissue was located on the posterior wall of the nasopharynx. All patients produced adenotomy and during the year they were under our supervision. Results. Each group consisted of 48 patients. After some time, due to frequent colds in all patients repeated the symptoms of adenoiditis. Subsequently these patients underwent adenotomy. Analyzing the results of treatment of adenoids, revealed the following: patients in whom the efficacy was assessed as unsatisfactory, in the anamnesis there was skin Allergy and various Allergy symptoms, frequent colds especially when visiting children’s groups. Conclusions. In the treatment of adenoiditis in pre - and postoperative period, the use of alkaline and antimicrobials influences the effectiveness of adenotomy, improves the postoperative period. On the effectiveness of treatment of adenoiditis more affected by the liquefaction of mucus and destruction of mucosal secretions than the use of antimicrobial agents. Allergic background has a great influence on the efficiency of treatment of patients with adenoiditis.